Whatever! - Gallagher, Diana G. (Gallagher, Diana G. Claudia Cristina Cortez., 2008)
It seems as if the Whatever Club is doomed when Adam insists on joining, then wants to play baseball or video games instead of reading magazines and doing other things thirteen-year-old Claudia and her girlfriends are used to doing.